DEVELOPMENT OF PBL MODEL-BASED STUDENTS’ WORKSHEET TO IMPROVE STUDENTS’ CRITICAL THINKING SKILL IN PHASE C - Fatkhur Rohman; Mia Azzahra; Pramudiyanti; Joko Supriono; Fitriyani; Romlah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Critical thinking skill is a skill that students need to have in the 21st century. When students have critical thinking skills, they are expected to be able to seriously understand, analyze, and process the information before making a decision. The research objective is to improve students' critical thinking skills through PBL-based worksheets on the subject of the human digestive system. This LKPD product was developed using the ADDIE model, which was tested at MIN 2 West Lampung. As many as 15 students were in the control class and 25 students were in the experimental class. The research results indicate that the validated LKPD based on the validity test analysis using Aiken reveals a score of 0.8210 in the valid category. The analysis of the practicality test indicates 85% for educators and 88% for students, both are in the very practical category. The product effectiveness analysis reveals an average pre-test score of 58.4 and an average post-test score of 83.2. The development of worksheets based on the PBL model has a significant influence on students' critical thinking skills.